Defining the Limits of Aiding and Abetting in Human Trafficking Offenses: A Victim Protection Perspective on High Court Decision No. 52/Pid.Sus/2024/PT Mam - Indy Kanaishia; Rugun Romaida Hutabarat (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Human trafficking is a transnational organized crime that poses a serious threat to human rights and frequently involves multiple actors with varying degrees of participation, including accomplices (medeplichtigheid). However, the legal interpretation of aiding and abetting and the corresponding scope of criminal liability continue to present challenges in law enforcement practice. This study aims to analyze the legal determination of aiding and abetting in human trafficking offenses under Indonesian criminal law and to formulate the limits of criminal liability for individuals who fulfill this element, while emphasizing victim protection as a primary objective. The study employs a normative legal research method using statutory, conceptual, and case-based approaches. The findings indicate that aiding and abetting in human trafficking requires the existence of actual assistance, intentional participation, and a functional connection between the assistance provided and the exploitation of the victim. Criminal liability should therefore be assessed based on the degree of culpability and the extent of an accomplice’s contribution to the trafficking network. The study concludes that clearer legal standards regarding aiding and abetting can strengthen efforts to combat human trafficking while enhancing the protection, recovery, and fulfillment of victims’ rights.